Challenges of social media workers in football clubs using technology–organization–environment (TOE) framework - Abed Mahmoudian; Behzad Izadi; Do Young Pyun (Future Business Journal)
Abstract This study, using the Technology–Organization–Environment (TOE) theory, attempts to identify the challenges faced by social media workers in the Persian Gulf Premier League (PGPL). Thematic analysis technique was used to analyze the data obtained from in-depth interviews with 21 social media workers in PGPL. The challenges of social media workers of football clubs were categorized into three main themes and fourteen sub-themes: technological (complexity of page management, weak infrastructure, time and workload, health threat, and weak compatibility), organizational (weak organizational structure, weak organizational culture, weak support from top management, limited financial resources, and limited human resources), and environmental challenges (competitive pressure, market trends and customer needs, weak laws and policies, and normative pressure). In the digital age, social media workers are crucial to the success of sport organizations' marketing strategies, and reducing their challenges in various areas can increase competitive advantage of sport organizations.